2006
DOI: 10.1002/ccd.20677
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score analysis of vascular complications after diagnostic cardiac catheterization and percutaneous coronary intervention 1998–2003

Abstract: In this large single-center, contemporary observational study, the risk-adjusted occurrence of vascular complications following VCD use for femoral artery access management is not increased by VCD use. Thus, in the current era, the benefit of VCD use is not offset by reduced safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 20 publications
0
53
0
5
Order By: Relevance
“…There has been a significant improvement in overall rates of complication among both men and women, however, women remain at a significantly higher risk. 21 Our current analysis represents one of the largest multicenter PCI reports in women and spans an era of contemporary practice. In parallel, but separate analysis of men and women undergoing PCI, clinical and procedural variables, such as older age, renal insufficiency, cardiogenic shock, and large sheath sizes were significant independent predictors of bleeding/VC in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a significant improvement in overall rates of complication among both men and women, however, women remain at a significantly higher risk. 21 Our current analysis represents one of the largest multicenter PCI reports in women and spans an era of contemporary practice. In parallel, but separate analysis of men and women undergoing PCI, clinical and procedural variables, such as older age, renal insufficiency, cardiogenic shock, and large sheath sizes were significant independent predictors of bleeding/VC in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…A number of meta-analyses and randomized and nonrandomized studies have shown variable results. Some studies have shown efficacy equivalent to that of manual compression, 24,25 and a few have shown superiority of these devices to manual compression. 26 -29 However, other studies have expressed concern about an increased risk of complications with these devices.…”
Section: Vascular Closure Devicementioning
confidence: 99%
“…Previous reports have shown that pseudoaneurysm develops from vascular wall damaged by catheterization, and secure astriction could prevent development of pseudoaneurysm [7]. Secured astriction can also reduce subcutaneous hemorrhage after catheterization, which is effective for decreasing median nerve palsy caused by hematoma following catheterization [7].…”
Section: Discussionmentioning
confidence: 99%